Radiografia digital para inspeção de soldas de dutos - Melhor sensibilidade - Moreira, Edson Vasques; Simões, Helena Ribeiro; Rabello, José Maurício Barbosa; De Camargo, José Rubens; Dos Santos Pereira, Marcelo [UNESP] (My University, 2008)
The conventional radiographic technique using industrial radiographic films is with the days finishing. The Digital Radiography is taking place in several sectors, e.g., the medical, aerospace, security, automotive, etc. In addition to representing a technological trend, it has been demonstrated that digital radiography offers a series of benefits in terms of productivity, sensitivity, environmental aspects, image treatment tools, cost reduction, etc. If one weld seam to be inspected is from a serried product, as example a pipe, the best option to be implemented is the Flat Panel Detector, with this equipment is possible to reduce the obtaining digital radiographic images in place of films and reducing the inspection cycle time due to its high degree of automation. In the experiments described in this paper, this new technique was tested and the results were compared with those obtained by the conventional radiography. The welded specimens were prepared using the submerged-arc welding process and small artificial cracks of the most varied dimensions, present in the specimens, were used to establish a comparison of the sensitivities presented by the techniques employed. After conducting several experiments, the digital method presented the highest sensitivity to the wire-type Image Quality Indicator (IQI) and in the detection of small defects, leading to the conclusion that the use of digital radiography using the flat-panel detector offers advantages over the conventional technique [1, 2]. This work was carried out based on the API 5L Edition 2004 [3] and ISO 3183 Edition 2007 [4] specifications.
Digital radiography to inspect weld seams of pipelines - Better sensitivity
Keywords: Digital radiography; Gas-lines; Industrial radiographic films; Oil-lines; Welding